Differential expression of Gnαq gene in white and black skin tissues of mice - Yin Zhihong; Xia Yu; Zhao Xin; Wang Zhun; Lu Jieli; Pang Quanhai (浙江大学学报. 农业与生命科学版)
Rich coat color is not only an important biological characteristics, but also a significant economic value for wool producing animals. Guanine nucleotide binding protein alpha q (Gnαq) is a downstream subunit of heterologous trimeric G protein. It plays a significant role in the performance of endothelin B receptor, which is involved in regulating coat hair of animals.In order to understand how Gnαq gene acts in the process of manipulating mammalian hair color, reverse transcription-polymerase chain reaction (RT-PCR) , quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting were used to detect the difference, the relative expression of Gnαq gene in different mice with two kinds of colors (white and black) . The localizations of Gnαq protein were analyzed by immunohistochemistry in different color skin tissues of mice.A partial sequence of Gnαq gene with the length of 140 bp was successfully amplified by PCR. Blasting in NCBI showed that the Gnαq sequence of mice had a high homology with other species, especially with rat and gray dwarf hamster, with the similarity of 98% and 92%, respectively. qRT-PCR and western blotting results showed that the relative expression of Gnαq mRNA and Gnαq protein in black skin of mice was significantly higher than those in the white skin of mice (P<0.01) . According to the results of immunohistochemistry, the Gnαq protein was expressed around the cells in hair follicles of mice, as well as in the outer root sheath and hair bulb of hair follicle.In conclusion, the expression of Gnαq is significantly different between the white and black skin tissues of mice, and it is distributed in the outer root sheath and hair bulb of hair follicle, suggesting that the Gnαq gene may play a critical role in the process of coat color formation in mice.